Respuesta :

The expression must contain x-terms and constants. A constant is a variable that never changes, which in this case would be x. These terms must combine to make 7x in total, and the whole sum should add up to 13.

We can put this into equation form like this: 

x + 3x + 3x = 13
x + 6x = 13
7x = 13

It can be in any other order as well, as long as it adds up to 7x like the problem states. If you wanted to, it could also look like this: (2x + 5x = 13) = 7x = 13.

If I am understanding your problem right, I believe this is correct. I hope it helps!